2020
DOI: 10.1002/mabi.202000228
|View full text |Cite
|
Sign up to set email alerts
|

Polydopamine‐Incorporated Nanoformulations for Biomedical Applications

Abstract: Polydopamine (PDA), a pigment in natural melanin, has attracted considerable attention because of its excellent optical properties, extraordinary adhesion, and good biocompatibility, which make it a promising material for application in energy, environmental, and biomedical fields. In this review, PDA‐incorporated nanoformulations are focused for biomedical applications such as drug delivery, bioimaging, and tumor therapy. First, the recent advances in PDA‐incorporated nanoformulations for drug delivery are di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 103 publications
(96 reference statements)
0
33
0
Order By: Relevance
“…In fact, PDA have found a much wider application as a coating on biocompatible/biodegradable nano‐ or microscale particles than modifying mucoadhesive properties of other macroscale systems such as hydrogels, nanofiber networks, films, or coatings. [ 129,130 ] This is further evidenced by the review article by Taipaleenmäki and Städler [ 131 ] that described the advances in polymers for intestinal mucoadhesion and mucopenetration applications in which PDA was mentioned only once (also see Table 1). It has been demonstrated that DA or catechol chain modified polymers including synthetic zwitterionic polymers [ 132 ] are more suitable for maintaining nonfouling surface conditions than PDA.…”
Section: Dopamine/catechols and Mucoadhesionmentioning
confidence: 96%
“…In fact, PDA have found a much wider application as a coating on biocompatible/biodegradable nano‐ or microscale particles than modifying mucoadhesive properties of other macroscale systems such as hydrogels, nanofiber networks, films, or coatings. [ 129,130 ] This is further evidenced by the review article by Taipaleenmäki and Städler [ 131 ] that described the advances in polymers for intestinal mucoadhesion and mucopenetration applications in which PDA was mentioned only once (also see Table 1). It has been demonstrated that DA or catechol chain modified polymers including synthetic zwitterionic polymers [ 132 ] are more suitable for maintaining nonfouling surface conditions than PDA.…”
Section: Dopamine/catechols and Mucoadhesionmentioning
confidence: 96%
“…One of the barriers to the development of OE employing melanin‐based components is that in contrast to naturally occurring biopolymers such as polynucleic acids (e.g., DNA/RNA) or polyamides (e.g., peptides/proteins) which have specific sequences of monomers and therefore reproducible properties if appropriately purified; melanins are a class of biopolymers which do not have a specific sequence of monomers and therefore their properties are not necessarily reproducible (akin to polysaccharides such as cellulose), however, this does not necessarily preclude their use in real world applications (e.g., as dyes for textiles). Potential solutions to this include careful cultivation of melanin producing species under controlled conditions (e.g., employing expertise in blue, brown, gray, green, white, and yellow biotechnology), wherein the environment is controlled (e.g., defined media for industrial scale fermentations of bacteria/yeast or industrial cultivation of cuttlefish/fungi), or indeed the development of melanin‐inspired synthetic analogues (e.g., polydopamine); [ 654,709–712 ] and balancing the necessity for high levels of reproducibility (e.g., biosensors for biomedical applications, electronics for long term biomedical/technical applications) with utility (e.g., dyes, components of degradable/transient electronics (e.g., batteries)).…”
Section: Melanins For a Sustainable Futurementioning
confidence: 99%
“…39–41 The excellent antibacterial properties of FeCo@PDA NPs are mainly due to the strong adhesion of FeCo@PDA NPs and the enhanced Fenton reaction activity under bimetallic catalysis. Specifically, firstly the bacterial membrane is destroyed and endogenous H 2 O 2 is released under the physical destruction of PDA NPs and Co 2+ , 25,42–45 then the released H 2 O 2 produces a large amount of reactive oxygen species under the synergistic catalysis of Fe 2+ /Co 2+ , which finally results in complete killing of the bacteria. 36–38 The results of the antibacterial activity test showed that the multi-mechanism synergistic antibacterial effect of bimetal loading was significantly better than that of single metal loading.…”
Section: Introductionmentioning
confidence: 99%